Incidence and Risk Factors for Pin Site Infection of Exposed Kirschner Wires Following Elective Forefoot Surgery. (October 2019) - McKenzie, James C.; Rogero, Ryan G.; Khawam, Sultan; McDonald, Elizabeth L.; Nicholson, Kristen; Shakked, Rachel J.; Fuchs, Daniel; Raikin, Steven M.
Background: Kirschner wires (K-wires) are commonly utilized for temporary metatarsal and phalangeal fixation following forefoot procedures. K-wires can remain in place for up to 6 weeks postoperatively and are at risk for complications. This study investigated the incidence of infectious complications of exposed K-wires after forefoot surgery and identifies risk factors for these complications. Methods: A single-surgeon retrospective chart review of forefoot surgeries from 2007 to 2017 was undertaken. Inclusion criteria were adult patients (≥18 years) undergoing elective forefoot surgery with the use of exposed K-wires. Incidence of pin site infectious complication, defined as cellulitis, or pin site drainage and/or migration/loosening of the pin was noted. Patient demographic and perioperative data were analyzed, along with the number of K-wires placed per procedure. Mann-Whitney U and chi-square tests were performed to determine predictive factors related to pin site infection rates, with a multivariable model with significant factors subsequently performed. Two-thousand seventeen K-wires in 1237 patients were analyzed. Results: There were 35 pin site infections for a rate of 1.74%. Combined forefoot procedures (507 pins in 229 patients) had a pin site infection rate of 4.93% (N = 25), followed by lesser metatarsal osteotomies (667 pins in 446 patients) at 1.05% (N = 7), then hammertoe corrections (694 pins in 421 patients) at 0.43% (N = 3), and no pin site infections with chevron osteotomies (149 pins in 141 patients). Male sex, body mass index (BMI), current smoker, and number of pins were significant risk factors ( P ≤ .05). Additionally, there were 23 non–infection-related K-wire complications. No long-term sequelae were encountered based on any complications. Conclusion: K-wires are commonly used for temporary immobilization of the smaller bones of the forefoot following deformity correction. Male sex, BMI, current smoker, and number of pins were significant risk factors for pin site infection, with a higher rate of infection with 2 or more pins placed. Level of Evidence: Level IV, case series.